Algoritmo de Descomposición Ciega Basado en el Modelo de Mezcla Multi-Lineal - Mendoza Chavarría, Juan Nicolás; Cruz-Guerrero, Inés Alejandro; Mejia-Rodriguez, Aldo Rodrigo; Campos-Delgado, Daniel Ulises (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Spectral unmixing has proven to be a great tool for the analysis of hyperspectral data, with linear mixing models (LMMs) being the most used in the literature. Nevertheless, due to the limitations of the LMMs to accurately describe the multiple light scattering effects in multi and hyperspectral imaging, new mixing models have emerged to describe nonlinear interactions. In this paper, we propose a new nonlinear unmixing algorithm based on a multilinear mixture model called Non-linear Extended Blind Endmember and Abundance Extraction (NEBEAE), which is based on a linear unmixing method established in the literature. The results of this study show that proposed method decreases the estimation errors of the spectral signatures and abundance maps, as well as the execution time with respect the state of the art methods.